1979
DOI: 10.1242/jeb.80.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurements of Instantaneous Lift in Desert Locust; Comparison with Jensen’s Experiments on Detached Wings

Abstract: Instantaneous values of lift in the locust Schistocerca gregaria, flying in a wind tunnel, were measured by means of a piezo-electric probe. The airflow velocity was adjusted to be equal to that which would have been experienced by the freely flying insect. In order to obtain the true aerodynamic forces, the inertial forces must be subtracted from the gross forces measured. These inertial forces were calculated from the movement of the centre of gravity and from the mass of the different wing se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…While Jensen's pioneering work [4] based on quasi-steady approach established the validity of steadystate aerodynamics in locust flight, he neither measured instantaneous forces including inertial forces nor did he investigate wing kinematics. Cloupeau et al [9] importantly found that the amplitude of instantaneous lift variation over a flapping cycle is much larger than obtained by Jensen, thus underlining the role of unsteady effects that were not accounted for in Jensen's experiments. They also carried out limited inertial force measurements (only in lift) using relatively less reliable technique to record the wing kinematics required to compute inertial forces.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…While Jensen's pioneering work [4] based on quasi-steady approach established the validity of steadystate aerodynamics in locust flight, he neither measured instantaneous forces including inertial forces nor did he investigate wing kinematics. Cloupeau et al [9] importantly found that the amplitude of instantaneous lift variation over a flapping cycle is much larger than obtained by Jensen, thus underlining the role of unsteady effects that were not accounted for in Jensen's experiments. They also carried out limited inertial force measurements (only in lift) using relatively less reliable technique to record the wing kinematics required to compute inertial forces.…”
Section: Introductionmentioning
confidence: 87%
“…These amplitude differences were attributed to the unsteady aerodynamic effects unaccounted for in Jensen's work [4]. Cloupeau et al [9] also determined inertial forces though limited only to vertical motion of the wing. The flapping motion of the wing with reference markers were filmed using a high speed video camera placed at a downstream location.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that they can fly hundreds of kilometres a day and migrate long distances across oceans [2]. This long-distance flight is mainly attributed to their two pairs of wings with different physiological functions: fore wings are used to control the direction of flight and the hind wings are used to provide most of the lift and thrust of the flight [3,4]. As a typical Orthoptera wing, the hind wing of the locusts consists of cross-veins, longitudinal veins and membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The results were then combined and compared to a locust flying in a wind tunnel (Jensen, 1956). In this case the results agreed well, but Cloupeau et al (1979) studied the cyclic force measurements for Schistocerca and showed that the quasi-steady principles were not suitable for this genus. Ellington (1984a,b,c,d,e,f) , re-examined the aerodynamics of hovering flight and found results that disagreed with Weis-Fogh and Jensen (1956).…”
Section: Aerodynamics Of Flapping Wingsmentioning
confidence: 73%